Produção, caracterização e dopagem de filmes finos de óxido de zinco sobre substrato de AU - (:unkn) unknown (Universidade Federal do Pampa, 2023)
As a source of clean and abundant energy, sunlight converted into electricity is a growing reality, which is replacing the use of fossil fuels. Among the various types of solar cells, which are devices produced with semiconductor material capable of converting solar energy into electrical energy, those based on thin films have great potential for manufacturing on an industrial scale due to the ease and low cost of production, which is why many researchers are committed to advancing this technology. This work aims to produce thin films of zinc oxide (ZnO) and aluminum-doped zinc oxide (AZO), for possible application in solar cells. For the development of this study, ZnO was synthesized by electrodeposition, on easily obtainable gold substrates (CDtrodes), for which two electrolytic solutions, variations in time, temperature and deposition and doping potentials with different aluminum concentrations were tested. The structural characterization of the films produced was carried out by X-ray diffraction (DRX), the morphological characterization by atomic force microscopy (AFM) and photoelectrochemical measurements (PEC) were carried out to analyze the semiconductor character obtained. It is hoped that this work will collaborate with research on the development of the second generation of photovoltaic cells, based on semiconductor thin films, in view of the technological advancement of these promising devices.
Keywords: Células fotovoltaicas; Filmes finos de ZnO; Dopagem de ZnO; CDtrodo; Difratometria de raios X; Microscopia de força atômica; Caracterização fotoeletroquímica; Photovoltaic cells; ZnO thin films; ZnO doping; CDtrodes; X-ray diffraction; Atomic force microscopy; Photoelectrochemical characterization; CNPQ::CIENCIAS EXATAS E DA TERRA